PRODUTIVIDADE ESTRATIFICADA DA MÃO DE OBRA: ESTUDO DE CASO EM OBRA DE PAREDES DE CONCRETO - Abreu, Marina; Lordsleem Jr, Alberto (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This work aims to analyze the stratified productivity during the assembly stage of armature, in the concrete walls system, at work in the metropolitan region of Recife. The case study consisted in the collection of data with direct observation in loco, using the study model of stratified productivity which allows the identification of factors influencing productivity and identification of how time is used. The RUPs of armature assembly ranged from 0.037 to 0.061 Man-hour/Kg, with mobilization, more specifically rebar transport, identified as the main influencing factor. It was also calculated the time use pattern in the work studied, where 66% of the time is used with direct work, 18% with mobilization, 9% with stops, 4% with support activities and 2% with displacements and activities related to the construction site. The main contributions of this work are the identification of factors that influence labor productivity and identification of the pattern of time use, generating opportunities for improvement.